High Temperature Thermal Properties of Columnar Yttria Stabilized Zirconia Thermal Barrier Coating Performed by Suspension Plasma Spraying. Issue 3 (September 2016) - Bernard, B; Schick, V; Remy, B; Quet, A; Bianchi, L
Abstract: Performance enhancement of gas turbines is a main issue for the aircraft industry. Over many years, a large part of the effort has been focused on the development of more insulating Thermal Barrier Coatings (TBCs). In this study, Yttria Stabilized Zirconia (YSZ) columnar structures are processed by Suspension Plasma Spraying (SPS). These structures have already demonstrated abilities to get improved thermal lifetime, similarly to standard YSZ TBCs performed by EB-PVD. Thermal diffusivity measurements coupled with differential scanning calorimetry analysis are performed from room temperature up to 1100 °C, first, on HastelloyX substrates and then, on bilayers including a SPS YSZ coating. Results show an effective thermal conductivity for YSZ performed by SPS lower than 1 W . m -1 K -1 whereas EB- PVD YSZ coatings exhibit a value of 1.5 W . m -1 K -1 .